Bronchiectasis Information and Education: a randomised, controlled feasibility trial - Katy L. M. Hester (Trials, 2020)
Abstract Background There has been comparatively little patient information about bronchiectasis, a chronic lung disease with rising prevalence. Patients want more information, which could improve their understanding and self-management. A novel information resource meeting identified needs has been co-developed in prior work. We sought to establish the feasibility of conducting a multi-centre randomised controlled trial to determine effect of the information resource on understanding, self-management and health outcomes. Methods/design We conducted an unblinded, single-centre, randomised controlled feasibility trial with two parallel groups (1:1 ratio), comparing a novel patient information resource with usual care in adults with bronchiectasis. Integrated qualitative methods allowed further evaluation of the intervention and trial process. The setting was two teaching hospitals in North East England. Participants randomised to the intervention group received the information resource (website and booklet) and instructions on its use. Feasibility outcome measures included willingness to enter the trial, in addition to recruitment and retention rates. Secondary outcome measures (resource use and satisfaction, quality of life, unscheduled healthcare presentations, exacerbation frequency, bronchiectasis knowledge and lung function) were recorded at baseline, 2 weeks and 12 weeks. Results Sixty-two participants were randomised (control group = 30; intervention group = 32). Thirty-eight (61%) were female, and the participants’ median age was 65 years (range 15–81). Median forced expiratory volume in 1 s percent predicted was 68% (range 10–120). Sixty-two of 124 (50%; 95% CI, 41–59%) of potentially eligible participants approached were recruited. Sixty (97%) of 62 participants completed the study (control group, 29 of 30 [97%]; 95% CI, 83–99%; 1 unrelated death; intervention group, 31 [97%] of 32; 95% CI, 84–99%; 1 withdrawal). In the intervention group, 27 (84%) of 32 reported using the information provided, and 25 (93%) of 27 of users found it useful, particularly the video content. Qualitative data analysis revealed acceptability of the trial and intervention. Web analytics recorded over 20,000 page views during the 16-month study period. Conclusion The successful recruitment process, high retention rate and study form completion rates indicate that it appears feasible to conduct a full trial based on this study design. Worldwide demand for online access to the information resource was high. Trial registration ISRCTN Registry, ISRCTN84229105 . Registered on 25 July 2014.